Magnitude and Determinants of Under-Nutrition Among Late Adolescent Girls in East Africa: Evidence From Demographic and Health Surveys (2010–2016) - Raru, Temam Beshir; Ayana, Galana Mamo; Kure, Mohammed Abdurke; Merga, Bedasa Taye; Yuya, Mohammed; Rob, Kedir Teji (Frontiers in Nutrition, 2022)
Introduction: Under-nutrition among late adolescent girls was a major public health problem in Sub-Saharan Africa (SSA) region. Among SSA countries Eastern African countries had problem of late adolescent female’s under-nutrition. Therefore, this study aimed to estimate the prevalence and determinants of under-nutrition among late adolescent girls in East Africa. Methods: A secondary data analysis was done based on 10 East African Countries Recent Demographic and Health Surveys. A total of 21,779 adolescent girls aged 15 to 19 years were included in the study. Cross tabulations and summary statistics were conducted to describe the study population. All bi-variable analyses yielding a p-value of ≤ 0.25 were retained for multi-variable model. A binary logistic regression model was fitted to determine factors associated with under-nutrition among late adolescent girls in east Africa. Variables with p-value of <0.05 in multivariable analysis were identified as statistically significant predictors of under-nutrition. Results: The overall magnitude of under-nutrition in east African countries was 16.50% (95% CI: 16.00-17.00). Whereas, the overall magnitude of obesity (over nutrition) in East African Country was 2.41% (95%CI: 2.21-2.62). Adolescent age 18-19 [AOR = 0.55; 95% CI; 0.51-0.60], secondary education [AOR = 0.79; 95%CI: 0.68-0.93], rich wealth index [AOR = 0.63; 95%CI: 0.56-0.69], medium wealth index [AOR = 0.80; 95%CI: 0.72-0.89], more than 7 house hold members [AOR =1.36; 95%CI;1.10-1.67], 30 minutes or longer to water source [AOR =1.10; 95%CI; 1.01-1.20], and living in Ethiopia [AOR =1.75; 95%CI: 1.51-2.03] were among factors significantly associated with under-nutrition. Conclusion: Under-nutrition in late adolescent girls remains considerable public health problem in East Africa. Age group, educational status, marital status, family wealth index, family size, time to water source, media exposure, and living country were significantly associated with under-nutrition. Therefore, devising strategies that improve socio-economic status of adolescents would help reduce the risks of under-nutrition.